Association Between Hygiene Level Among Diabetic Ulcer Patients and the Incidence of Methicillin-Resistant Staphylococcus aureus (MRSA) Infection - Lestari, Windy; Kurniawan; Mulyanto , Arif; Handayani , Farida Dwi (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the association between hygiene level and the incidence of Methicillin-Resistant Staphylococcus aureus (MRSA) infection in diabetic ulcers. An analytical observational study with a cross-sectional approach was conducted. The study included 20 patients with diabetic ulcers at RSUD Prof. Dr. Margono Soekarjo Purwokerto, selected using an accidental sampling technique. Bacterial identification was performed through culture on Mannitol Salt Agar (MSA), Gram staining, biochemical tests, and antibiotic susceptibility testing using the disk diffusion method. MRSA identification was determined based on cefoxitin susceptibility testing. Hygiene levels were assessed using an observation checklist developed based on wound care principles and WHO guidelines. Data were analyzed using Fisher’s Exact test with a significance level of p < 0.05. Among the 20 patients with diabetic ulcers, MRSA infection was identified in 17 patients (85%), while 3 patients (15%) were not infected with MRSA. In the group with good hygiene practices, 2 patients (10%) were infected with MRSA and 3 patients (15%) were not infected, whereas among patients with poor hygiene practices, 15 patients (75%) were infected with MRSA. Statistical analysis revealed a significant association between hygiene level and MRSA infection incidence (p = 0.009). These findings indicate that hygiene practices in diabetic ulcer care are associated with the occurrence of MRSA infection among patients with diabetic ulcers.